Paico y albendazol en el manejo de ascardiasis y giardiasis en las Escuela Manuel de Jesús Macas de San Lucas - Loja - Cartuche Mayta, Jessica Katherine (2019)
Traditional medicine today continues to play an important role in health care. In our country, especially in the province of Loja, the practice of traditional medicine has not disappeared, being applied to the treatment of different pathologies. Frequently, for the treatment of intestinal parasitism; as it is one of the predominant public health problems that most often affects children of school age. On the basis of these precedents, the objective of de present investigation was to determine the therapeutic effect of albendazole and paico in the management of ascaridiasis and guardiasis in schoolchildren of the Parish San Lucas of the Loja Canton; for this purpose, a study was carried out with a quantitative, descriptive, transversal and quasi experimental type approaches in 54 children between the ages of 5 and 12 years enrolled and attending regular classes at Manuel de Jesus Macas school. By non-probabilistic sampling at the convenience of the investigator; prior informed consent signed by each of the children's representatives, a stool testing was conducted of each of the schoolchildren in the sample to identify those presenting the types of parasites to be studies. Once the requirement was met, they were divided into two groups; to the first group included those parasitized whit ascaris lumbricoides and to second group those who present giardiasis, to half of each established group it was given albendazole and to the remaining paico. For the statistical analysis, tables mapped out in the IBM SPSS Statistics program and Microsoft Excel 2013 were used, this revealed that according to age and sec there is a predominance of parasitism in schoolchildren between 11 and 12 years of age with a total of 6 cases representing 37.5%; in terms of gender, the predominance of ascaridiasis and giardiasis is present in girls with a figure of 11 cases equivalent to 68.8%. In terms of effectiveness, the treatment with albendazole for both ascaridiasis and giardiasis was effective in all the cases applied constituting 100%. With respect to paico this proved effective in all cases of giardiasis; meanwhile that for ascaridiasis its effectiveness reached 25%. In relation to adverse effects following treatment with albendazole and paico; these were not presented to any of the particpants. Key words: Efficacy, parasitosis, traditional medicine, western medicine.